A multi-agent system for distributed maintenance scheduling. (July 2019) - Hedjazi, Djalal; Layachi, Fateh; Boubiche, Djallel Eddine
Highlights : A new distributed approach for corrective maintenance scheduling problem is proposed. The proposed approach enables decision-making for subcontractors in distributed maintenance environment under uncertainty. The proposed approach takes into account the skill level of the resource to represent the imprecise character of the processing time for the maintenance activity and resource. The proposed approach is implemented and evaluated by using multi-agent system and a global schedule can be obtained through interaction among the different agents. The proposed approach produces high-quality schedule in terms of Global Cost, Total Weighted Tardiness Cost and makespan compared to WSPT-H-EDD method. Abstract: Due to the intrinsically geo-distributed subcontracting maintenance activity practice, the maintenance scheduling has for a long time been a major challenge in the industry. This research work presents a methodology to schedule the maintenance activities of geo-distributed assets. A multi-agent system based approach is proposed to enable the decision-making for the subcontractors in a distributed industrial environment under uncertainty. An auction based negotiation mechanism is designed to promote competition and cooperation among the different agents, and to obtain global good schedule.Compared to the Weighted Shortest Processing Time first–Heuristic–Earliest Due Date ( WSPT-H-EDD ) method,  the experimental results show that the proposed approach is able to provide scheduling scheme with good performances in terms of Global Cost, Total Weighted Tardiness Cost and makespan.